(3GdQjGV GdCcHQs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg TcQG dfYeJg Efi bO PcQJ ai cJHi CMhGd GdUfYI GdJi jSejgG GdYGeI GdcjejGA s
(3BNQgG (B:s
(3aeG CQOfG HgPG EdG hLg Gddg hGdOGQ GdBNQI aEfg hdi cd EMSGf hefJgi cd QZHI hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B95 - (3U(B119s
(3GdfSNI HgG MhGTs
(3eQJH Ydi YTQjf ebGdI hcd ebGdI Ydi CHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
Keywords: (3GdcjejGA h GdWHjYjGJs